Integrating ICT into Islamic Religious Education to Internalize Multicultural Values in Pesantren-Based Vocational Schools - Mukhamad Masyhuri; M. Jamhuri; M. Anang Sholikhudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The rapid advancement of information and communication technology (ICT) has transformed students' learning environments, yet the internalization of multicultural values in Islamic Religious Education (IRE) remains insufficiently integrated into technology-supported learning. IRE instruction often emphasizes cognitive achievement, while values such as tolerance, equality, mutual respect, and social responsibility receive less attention in digital learning practices. This study aims to analyze the integration of ICT into Islamic Religious Education for the internalization of multicultural values as an effort to strengthen students' character at SMK Pesantren Terpadu Dlanggu Mojokerto. A qualitative approach with a descriptive case study design was employed. Data were collected through classroom observations, semi-structured interviews, and documentation involving the principal, vice principal for curriculum, Islamic Religious Education teachers, and students. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing, while trustworthiness was ensured through source triangulation, technique triangulation, member checking, and prolonged engagement. The findings reveal that multicultural values were internalized through three interconnected stages: value transformation, value transaction, and value transinternalization. ICT integration enabled teachers to present multicultural values through digital presentations, videos, images, and contextual learning resources, while reflective dialogue and collaborative learning encouraged students to translate Islamic values into everyday social practices. The study demonstrates that ICT functions not only as an instructional medium but also as a pedagogical instrument for character formation, contributing to the development of multicultural Islamic education in pesantren-based vocational schools.